2010
DOI: 10.1071/an09033
|View full text |Cite
|
Sign up to set email alerts
|

Genetic (co)variances between wrinkle score and absence of breech strike in mulesed and unmulesed Merino sheep, using a threshold model

Abstract: Heritability estimates for, and genetic correlations among neck wrinkle score, body wrinkle score, breech wrinkle score and the absence of breech strike were determined on 2918 16-month hoggets from a selection experiment with South African Merinos. Data were obtained from the lamb drops of 9 years between 1998 and 2007, born as the progeny of 247 sires and 1250 dams. All progeny born until 2002 were subjected to the Modified Mules operation as lambs (n = 1799). However, due to international pressure to phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 22 publications
4
11
1
Order By: Relevance
“…This estimate is slightly higher than the value estimated by Scholtz et al (2010) for absence of breech strike, but significantly higher than the heritability of 0.32 reported by Smith et al (2009) for breech strike. These differences in heritability estimates could possibly have been caused by different fly strike frequencies and different models, and also because Smith et al (2009) treated breech strike as a continuous trait, whereas Scholtz et al (2010) treated breech strike as a threshold trait, as was done in the present study. As this flock was composed of sheep from different unrelated genetic sources, strain or origin of flock effects could also have contributed to the higher heritability of breech strike in spite of the fact that the property of origin was fitted in the model to accommodate genetic groups.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…This estimate is slightly higher than the value estimated by Scholtz et al (2010) for absence of breech strike, but significantly higher than the heritability of 0.32 reported by Smith et al (2009) for breech strike. These differences in heritability estimates could possibly have been caused by different fly strike frequencies and different models, and also because Smith et al (2009) treated breech strike as a continuous trait, whereas Scholtz et al (2010) treated breech strike as a threshold trait, as was done in the present study. As this flock was composed of sheep from different unrelated genetic sources, strain or origin of flock effects could also have contributed to the higher heritability of breech strike in spite of the fact that the property of origin was fitted in the model to accommodate genetic groups.…”
Section: Discussioncontrasting
confidence: 49%
“…The highest wrinkle scores were recorded on the neck of the animals. Scholtz et al (2010) showed that neck wrinkle is genetically strongly correlated with breech wrinkle in mulesed (r g = 0.80) and unmulesed (r g = 0.89) sheep. They also found a stronger genetic relationship between the absence of breech strike and neck wrinkle (r g = -0.57) in unmulesed sheep than that between the absence of breech strike and breech wrinkle (r g = -0.45), which strongly agrees with the results of the present study.…”
Section: Genetic Correlations Between Breech Strike and Indicator Traitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Research by Scholtz et al (2010b; suggested sufficient genetic variation on the underlying liability scale where breech flystrike of Merinos is concerned. The presence of significant genetic variation in breech strike is supported by marked line differences in its frequency in lines of Merino sheep divergently selected for number of lambs weaned per ewe joined (Scholtz et al, 2010a).…”
Section: Resistance To Stressorsmentioning
confidence: 99%